(untitled) (Eurasian Research Bulletin, 2024)
In this article, by gradually reducing the monopoly in the goods and financial markets in our Republic, further reducing the negative impact on the competitiveness of the economy, increasing the efficiency of the system of granting privileges and preferences, as well as reducing the regulatory burden on business entities and implementing the tax administration of taxpayers and special attention is being paid to the fundamental improvement of service provision on the basis of mutual cooperation on the fulfillment of tax obligations